Pemikiran Hukum Yusuf Qardhawi Tentang Sanksi Bagi Muzakki Yang Tidak Membayar Zakat - Purnama, Hamdan (Jurnal Hukum In Concreto, 2023)
Zakat is the obligation of every Muslim who fulfills the conditions to give a portion of his income or wealth to those who are entitled, according to the provisions of Islamic law. In conducting this research, the authors used a normative approach, namely an approach based on the verses of the Qur'an and Hadith as well as the opinions of the scholars regarding the principles of Fiqhiyah Ma'nawiyah, namely understanding plural texts through the skills of their meanings and using the approach socio-historical through studying the background of the life of the character discussed in this case is Yusuf Qardhawi. The technology for tracking legal materials is based on literature studies. The data analysis method used in making this work is logical thinking. The search results show that Yusuf Qardhawi asked that a muzak be given a sanction for not paying zakat, so a warning must be given. When warning after warning failed, he had to be delivered into the hands of the authorities with a lawful whip so that he could do his job. The Istinbath-Muzak that Yusuf Qardhawi legally uses for the obligation to pay zakat is the use of Ijtihad Tarjih. Yusuf Qardhawi's reason for imposing sanctions on muzakki who do not pay zakat is that zakat is one of the main taxes in Islam. A philanthropist Muslim who is required by applicable law to spend Zakat from his wealth for the benefit of the people.